1956
DOI: 10.1042/bj0630618
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of short-chain fatty acids in the sheep. 4. The pathway of propionate metabolism in rumen epithelial tissue

Abstract: system at the stage of cytochrome c reductase; the diaphorase activity is not affected. 7. Thiol compounds react chemically with fluoropyruvate, thereby preventing its inhibitory activity. The reaction products show characteristic spectra in the ultraviolet region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1958
1958
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The ®nding by Masson & Phillipson (1951) that the proportion of butyrate in portal-blood SCFA was much lower than in ruminal SCFA prompted the pioneering studies of R. J. Pennington and his colleagues on the metabolism of SCFA by rumen epithelium in vitro (Pennington, 1952(Pennington, , 1954Annison & Pennington, 1954;Pennington & Sutherland, 1956). Butyrate and propionate were shown to be extensively metabolized, but acetate, n-valerate and the branched-chain SCFA were all utilized to some extent by rumen epithelium.…”
Section: Utilization Of Short-chain Fatty Acids By the Portal-drainedmentioning
confidence: 99%
“…The ®nding by Masson & Phillipson (1951) that the proportion of butyrate in portal-blood SCFA was much lower than in ruminal SCFA prompted the pioneering studies of R. J. Pennington and his colleagues on the metabolism of SCFA by rumen epithelium in vitro (Pennington, 1952(Pennington, , 1954Annison & Pennington, 1954;Pennington & Sutherland, 1956). Butyrate and propionate were shown to be extensively metabolized, but acetate, n-valerate and the branched-chain SCFA were all utilized to some extent by rumen epithelium.…”
Section: Utilization Of Short-chain Fatty Acids By the Portal-drainedmentioning
confidence: 99%
“…Propionate is converted to lactate via succinate, a symmetrical intermediate of the tricarboxylic acid cycle (Pennington & Sutherland, 1956b). Thus lactate formed from [2-^^C]propionate will be equally labeled in C-2 and C-3 and have the same specific radioactivity as pro pionate.…”
Section: Discussionmentioning
confidence: 99%
“…In calculating the extent of metabolism by the epithelium of the ruminoreticulum it was assumed that propionate was converted to no major metabolite other than lactate. It has been shown that lactate accumulates as the major product during incubations of rumen epithelium with propionate (Pennington & Sutherland, 1956b;Taylor & Ramsey, 1965;Welgand et al 1967). Pyruvate is not likely to be a major metabolite i^ vivo since the concentration of pyruvate in bovine blood is very much lower than that of lactate (Dunlop, Hammond & Stevens, 1964).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH values for fecal samples were between 6.0 and 6,5 (measured 60 ^This indicates 1st, 2nd and 3rd defecations after administration of C -sucrose.…”
Section: 1mentioning
confidence: 99%